2009
DOI: 10.1103/physreve.79.051120
|View full text |Cite
|
Sign up to set email alerts
|

Solvable stochastic dealer models for financial markets

Abstract: We introduce solvable stochastic dealer models, which can reproduce basic empirical laws of financial markets such as the power law of price change. Starting from the simplest model that is almost equivalent to a Poisson random noise generator, the model becomes fairly realistic by adding only two effects: the self-modulation of transaction intervals and a forecasting tendency, which uses a moving average of the latest market price changes. Based on the present microscopic model of markets, we find a quantitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 40 publications
6
53
0
5
Order By: Relevance
“…Other approaches simulate financial markets with computational economic models with different class of agents' strategies or using the statistics of buy and sell orders from the viewpoint of statistical physics [21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Other approaches simulate financial markets with computational economic models with different class of agents' strategies or using the statistics of buy and sell orders from the viewpoint of statistical physics [21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…[18] Moreover, the PUCK model is theoretically shown to include ARCH/GARCH models as a special limit of random up-down cases, [19] and it is also known to be applicable to macro-limit behaviours of markets such as exponential or double-exponential rises of prices observed at inflation or hyperinflation. [20] Furthermore, it is shown by Takayasu et al [21] and Yamada et al [22][23][24] that repulsive market potential force is observed in an artificial market when trend-followers are the majority who predict near future market price by extending a trend-line. As the form of potential force can be determined from the data, the model is used as a real-time risk estimator of financial markets.…”
Section: Introductionmentioning
confidence: 94%
“…This model is based on the Ising model. Moreover, other studies have investigated agencybased models focusing on dealer behavior [8] [13]. In addition to simulations, numerous studies have conducted empirical analysis using actual market data [15] [20].…”
Section: Modelmentioning
confidence: 99%